2015
DOI: 10.1021/acsami.5b06675
|View full text |Cite
|
Sign up to set email alerts
|

Folded Elastic Strip-Based Triboelectric Nanogenerator for Harvesting Human Motion Energy for Multiple Applications

Abstract: A folded elastic strip-based triboelectric nanogenerator (FS-TENG) made from two folded double-layer elastic strips of Al/PET and PTFE/PET can achieve multiple functions by low frequency mechanical motion. A single FS-TENG with strip width of 3 cm and length of 27 cm can generate a maximum output current, open-circuit voltage, and peak power of 55 μA, 840 V, and 7.33 mW at deformation frequency of 4 Hz with amplitude of 2.5 cm, respectively. This FS-TENG can work as a weight sensor due to its good elasticity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 28 publications
0
36
0
Order By: Relevance
“…Triboelectric nanogenerators (TENGs) that work based on triboelectrification has been proved effective for harvesting random mechanical energy from the environment, such as water wave energy, acoustic energy, and mechanical energy from human motion, and converting them to electricity . The TENGs have also been demonstrated as powerful self‐powered sensors for monitoring the movement of human body .…”
Section: Introductionmentioning
confidence: 99%
“…Triboelectric nanogenerators (TENGs) that work based on triboelectrification has been proved effective for harvesting random mechanical energy from the environment, such as water wave energy, acoustic energy, and mechanical energy from human motion, and converting them to electricity . The TENGs have also been demonstrated as powerful self‐powered sensors for monitoring the movement of human body .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that there is a strong correlation between output performance and the contact/separation synchronism for a multi-layer TENG. 36,43,44 Due to the complete synchronization of an ideal spring, the current-time waveform of a TENG with a spring structure should be in accord with the normal waveform from a single-layer TENG. To verify the contact/separation synchronization of the SL-TENG devices, a comparison study between a SL-TENG and a typical singlelayer TENG was performed, as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To overcome the insufficient energy output by a single-layer TENG, some integrated multi-layer TENGs were studied and reported. [40][41][42][43][44][45] However, owing to usage of skeleton materials, most previous multi-layer devices had a relatively large volume, [40][41][42] which subsequently limits their wide application in TENGs. Moreover, the contact/separation asynchronism derived from each pair of triboelectric materials in a device [43][44][45] leads to the presence of partial current peaks on the output current-time waveform.…”
Section: Introductionmentioning
confidence: 99%
“…There are abundant successful studies on harvesting wasted energy to serve human daily living, like wind, solar, thermal, mechanical, and chemical energy. By using a new, successful triboelectric nanogenerator (TENG) technology, wasted energy from motion, [1,2] sliding, [3,4] vibration, [5,6] hydraulic, [5,7] or air power [8] have received much attention for effectively harvesting energy to successfully use DOI: 10.1002/smll.201700373 The triboelectric generator (TEG) is a cost-effective, multi-fabricated, friendly mechanical-energy-harvesting device. The traditional TEG, generally formed by two triboelectric materials in multilayers or a simple pattern, generated triboelectricity as it worked in the cycling contact-separation operation.…”
Section: Introductionmentioning
confidence: 99%
“…The traditional TEG, generally formed by two triboelectric materials in multilayers or a simple pattern, generated triboelectricity as it worked in the cycling contact-separation operation. This paper demonstrates a novel, high-aspect-ratio, microneedle (MN)-structured polydimethylsiloxane (PDMS)-based triboelectric generator (MN-TEG) by means of a low-cost, simple fabrication using CO 2 in a tremendous amount of practical applications, including consumer electronics, [9] biosensors, [10] pressure sensors, [11] humidity sensors, [12] and portable electronic devices. [13] Most traditional triboelectric generators are based on a frictional concept in the contacting-releasing working cycle of two triboelectric materials in multilayers or simple patterns.…”
Section: Introductionmentioning
confidence: 99%